Impact of Voltage Violation Penalty Cost on Distribution System Operation Considering Electric Vehicle - Ebrahimi, Mahoor; Ebrahimi, Mahan; Laaksonen, Hannu; Shafie-khah, Miadreza (IEEE, 2023)
In the future, the widespread adoption of electric vehicle parking lots (EVPLs) may introduce operational challenges like voltage limit violations in distribution networks. However, EVPLs can potentially relieve these voltage limit violations by acting as flexible loads and providing reactive power support. In this paper, the impact of EVPLs on the optimal operation of the distribution network is investigated with a focus on their potential capability for reactive power support in a scenario that the distribution system operator (DSO) is committed to pay a penalty cost to customers if voltage limits are violated. Our results show that flexible charging of Electric Vehicles (EVs) and reactive power support from EVPLs, especially in the case where there exists a penalty cost for voltage violation, has a major impact on reducing the system cost. It can also pave the way for deploying more generation from distributed generation (DG) and renewable energy sources (RES) as well as reducing the voltage violation penalty costs.
Keywords: EV Parking Lot; Reactive Power Support; Voltage Violation Cost; Distribution System Operation; fi=Sähkötekniikka|en=Electrical Engineering|